Blue exorcist. 29 - Katō, Kazue, 1980- (Shonen Jump manga., 2024)
"Rin and his exorcist classmates are caught in a secret war against the forces of darkness. Raised by Father Fujimoto, a famous exorcist, Rin Okumura never knew his real father. One day a fateful argument with Father Fujimoto forces Rin to face a terrible truth--the blood of the demon lord Satan runs in Rin's veins! Rin swears to defeat Satan, but doing that means entering the mysterious True Cross Academy and becoming an exorcist himself. The Knights of the True Cross and the Exwires have fully engaged Satan on all fronts. Rin has confronted Satan head-on, and despite being blown apart, Rin's own demonic nature allows him to reform and stay in the fight. Now, Shemihaza begins a ritual to crystallize and trap Satan--a ritual that Shiemi will play a crucial part in. When Satan takes his transformation to the next level, even time itself warps under his power, showing everyone a future they could never have imagined..."--Goodreads.com.